Catfish (pangasius hypophthalmus) protein concentrat fortification in brownies cake - Wirda Hayati; Dewita Buchari; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was intended to evaluate consumer acceptance of brownies cakefortified with catfish (Pangasius hipophthalmus) protein concentrat. Four brownies cake weremade from a mixture of 12% wheat flour, 36% eggs, 10% chocolate ,24% sugar, 15%margarine, 0,1% vanila dan 0,06% salt. Each cake then was fortified with catfish proteinconcentrat at a level of 0%, 5%, 10% and 15% of wheat flour. Brownies cakes wereecaluated for consumer acceptance and proximate composition (moisture, protein and fat).The results showed that the cake fortified with 10% catfish protein concentrat was the mostpreferable by the consumer. Protein compotition of brownies cake fortified with 0%, 5%,10%and 15% of catfish protein concentrat was 8,04%, 16,12%, 19,27% and 21,05% respectively;fat was 19,50%, 16,56%, 16,01% and 15,59% respectively; and moisture was 30,47% ,29,17%, 27,98% and 27,20% respectively.Keyword: brownies cake, catfish (Pangasius hypopthalmus) protein concentrat, fortification.